The Relationship between Frequency of High-Sugar, Salt and Fat Food Consumption and The BMI in Adolescents - Jokomarsono, Elisabet Puspita; Probandari, Ari; Wiboworini, Budiyanti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: To identify and analyze preliminary data on the consumption habits of sugar, salt, and fat and their relationship to the Body Mass Index (BMI) in adolescents.Methodology: Observational study with a cross-sectional approach to high school adolescents in Surakarta. The number of incidental respondents aged 15-18 years was 31 students. Data on the characteristics of research respondents were obtained through questionnaires and the frequency of high-sugar, salt, and fat food consumption used the FFQ. Statistical data analysis of sugar and fat consumption on BMI using Fisher Exact and salt consumption on BMI using Chi-Square showed a p-value <0.05.Results: The descriptive analysis results indicated that 61.3% of adolescents often consumed high-sugar foods and drinks, bivariate statistical analysis results showed a p-value of 0.026 (<0.05), meaning that there was a relationship between the frequency of high-sugar food and drink consumption and BMI in adolescents. 38.7% of adolescents often consumed high-fat food and drinks, meaning that there was a relationship between the frequency of high-fat food and drinks consumption and BMI with a p-value of 0.026 (<0.05). 54.8% of adolescents often consumed high-salt foods. However, based on the results of statistical tests, there was no relationship between the frequency of salt consumption and BMI as shown by a p-value of 0.889 (>0.05). Applications/Originality/Value: The differences in research respondents, period and results that provide empirical evidence as the basic for the research to be carried out on the frequency of high sugar, salt, fat food consumption and the BMI of High School adolescents.